Dynamic effects of external debt accumulation on public capital formation and economic growth: Empirical evidence from Nigeria / Ibrahim Mohammed Adamu - Ibrahim Mohammed , Adamu (2017)
This thesis investigates empirically the dynamic effects of external debt accumulation on public capital formation, and economic growth in Nigeria annually over the period 1970–2013. The study deploys three equations for debt, investment and growth, respectively, and is augmented with debt and policy variables to analyse external debt issues in Nigeria. Following the confirmation of the order of integration, the analysis is based on Johansen multivariate cointegration approach and Vector Error Correction Model (VECM). Two dummies are incorporated in both cointegration test and short run analysis to account for exchange rate devaluation after the 1986 economic reform and the 2005 debt relief. External debt composite index was constructed by the principal component method (PCM) to capture the overall effect of external debt on economic growth. The results from the debt equation suggest that oil price, domestic savings and fiscal deficits are significantly correlated with external debt. In addition, the dummy variables for exchange rate and debt relief incorporated to capture the government reform policy and the effects of debt relief are also significant. Therefore, all the variables contribute to external borrowing in Nigeria. The results from the investment equation reveal that the external debt, debt service payment, foreign direct investment and dummy for real exchange rate affect public investment negatively. Only dummy for debt relief influences public investment positively. In the growth equation, a significant and negative effect of external debt composite index, domestic credit and dummy for real exchange rate on growth was found while the human capital and dummy for debt relief showed a positive effect on growth. In spite of the fact that Nigeria had the least external debt ratios from 2006 onwards compared to the past decades when its debt ratios reached unsustainable levels, it has still affected investment and growth negatively. The results of this thesis are consistent with the economic theories that argue that external loans retard investment and economic growth in the developing countries. Furthermore, the results also confirm that Nigeria is on the verge of returning to debt overhang status. Hence, appropriate measures have to be put in place to avoid future debt distress. This important finding that external debt has a negative impact on investment and growth suggests that relying on external debt to enhance economic growth is not a good policy. Hence, Nigeria should focus on its productive sectors, particularly the non-oil sectors that have been neglected, which could augment domestic resources through export earnings so that over dependence on oil and external loans can be reduced.